Thermodynamics of liquid Cu-Sn alloys - Chatterjee, S. K.; Prasad, L. C. (Journal of Nepal Chemical Society, 2006)
The large deviation from the ideal mixture behavior and concentration dependent asymmetry in the thermodynamic properties of Cu3Sn liquid alloys is investigated within a simple theoretical model of heterocoordination (i.e. a model in which there is a preference for unlike atoms pairing as nearest neighbors). The analysis suggest that hetero coordination leading to the formation of chemical complexes Cu3Sn is likely to exist in the melt but is only of a weakly interacting nature. The system exhibits almost ideal behavior at Sn-rich end. DOI: 10.3126/jncs.v21i0.218 Journal of Nepal Chemical Society Vol.21 2006 pp.26-29